2008
DOI: 10.1093/ndt/gfn339
|View full text |Cite
|
Sign up to set email alerts
|

Daily oral 25-hydroxycholecalciferol supplementation for vitamin D deficiency in haemodialysis patients: effects on mineral metabolism and bone markers

Abstract: With a daily dose ranging from 10 to 30 microg, daily oral 25(OH)D(3) supplementation corrects most vitamin D deficiencies or insufficiencies in HD patients, without any evident toxicity. The main effects observed included correction of excessive bone turnover, despite less alfacalcidol administration, increase in serum albumin level and increase in the percentage of patients with serum calcium and phosphorus levels within the recommendation of the KDOQI guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 47 publications
5
91
2
4
Order By: Relevance
“…Calciferol therapy has been reported to improve parameters of mineral metabolism in observational studies, with associations to decreased parathyroid hormone (PTH) and b-ALP levels (2,24,25). However, treatment allocation did not influence values of iPTH, ALP, or b-ALP in this study.…”
Section: Mineral Metabolism and Bone Turnovercontrasting
confidence: 67%
See 1 more Smart Citation
“…Calciferol therapy has been reported to improve parameters of mineral metabolism in observational studies, with associations to decreased parathyroid hormone (PTH) and b-ALP levels (2,24,25). However, treatment allocation did not influence values of iPTH, ALP, or b-ALP in this study.…”
Section: Mineral Metabolism and Bone Turnovercontrasting
confidence: 67%
“…Patients with CKD on dialysis (CKD-5D) frequently have low 25(OH)D levels, varying from ,10 ng/ml (25 nmol/L) in 65% of patients in one study (2), to levels ,15 ng/ml (37.5 nmol/L) in 14%-23% of patients in other studies (3,4). Patients on dialysis lack normal renal conversion of 25(OH)D to 1,25-dihydroxyvitamin D [1,25(OH) 2 D], and evidence to support the benefits of increasing 25(OH)D levels with calciferol (cholecalciferol or ergocalciferol) is weak.…”
Section: Introductionmentioning
confidence: 96%
“…To confirm this, several studies have shown that native vitamin D3 (cholecalciferol) supplementation improves 25-hydroxyvitamin D3 and 1,25-dihydroxyvitamin D3 levels in dialysis patients (85)(86)(87). PTH level was significantly reduced by 20-35% from baseline in two studies although there was no placebo group for comparison (85,86). One RCT on 42 haemodialysis patients over 15 weeks did not show significant change in PTH with cholecalciferol compared to placebo (87) whereas a more recent RCT on 43 haemodialysis patients by Delanaye et al showed statistically significant reduction in PTH with cholecalciferol whilst PTH was increased in the placebo group over a oneyear period (90).…”
Section: Native Vitamin Dmentioning
confidence: 96%
“…To confirm this, several studies have shown that native vitamin D3 (cholecalciferol) supplementation improves 25-hydroxyvitamin D3 and 1,25-dihydroxyvitamin D3 levels in dialysis patients (85)(86)(87). PTH level was significantly reduced by 20-35% from baseline in two studies although there was no placebo group for comparison (85,86).…”
Section: Native Vitamin Dmentioning
confidence: 98%
See 1 more Smart Citation